METACOGNITIVE STRATEGY AND STUDENT’S READING COMPREHENSION: AN EXPERIMENTAL STUDY AT SMK N 1 KOTA BENGKULU - Syafrianti, Herlina; Suwarno, Bambang; ., Elfrida (Journal of English Education and Teaching, 2018)
This research aimed to know the effect of using metacognitive strategy towards student’s reading comprehension. The design was quasi-experimental. The sample consists of 69 students in two classes. The instrument consists of reading test which was tried out. The treatment for the experiment group was metacognitive strategy and for the control group was the strategy that the teacher use in the class. The data were collected through pre-test and post-test. The activity in the classroom during six meetings, two meetings for pre-test and post-test and four meetings for teaching in the classroom. The data was analyzed by The Wilcoxon Test and The Mann-Whitney Test. The Wilcoxon Test for the control group showed that there was no significant difference between pre-test and post-test. The Wilcoxon test for the experiment group showed that there was significant difference between pre-test and post-test. The Mann-Whitney test for pre-test showed that there was no significant difference between experiment and control class. The Mann-Whitney test for post-test showed that there was significant difference between experiment and control class. Finding of the research showed that, there was significant difference between pre-test and post-test for the experiment class and there was significant differece between experiment and control class for post-test result. This result indicated that there was an effect of metacognitive strategy towards student’s reading comprehension